The features of beta-cells organization in the pancreas of spontaneously hypertensive rat (SHR) - T. V. Abramova; Yu. M. Kolesnyk (Patologìâ)
The control of b-cells pool in patients with hypertension is an actual problem, as it is possible that the hereditary genetic defects of arterial hypertension formation may affect the mechanisms of endocrine cell mass maintenance in pancreas and cause disruption of glucose metabolism and diabetes. In addition, violation of cytoarchitectonics of pancreatic islets may affect the adequate insulin secretion by the pancreas. This could be provoked by regional blood flow violations in patients with hypertension.